Access to oral health care – an Australian perspective* - Schwarz E. (Blackwell Synergy, 2006)
The objectives of this paper are to give a brief description of the Australian context for its dental care services and to discuss some of the nationally recognized issues in access to dental care with special reference to the situation in the most populous state, New South Wales